Fuzzy and Sliding Mode Variable Structure Control of Vehicle Active Steering System - Qi, Gengxin; Fan, Xiaobin; Zhao, Zixiang (Recent Patents on Mechanical Engineering, 2021)
Background: The safety of vehicles has been valued throughout the world, whether it is now or in the future, the automobile safety issue is the hotspot and focus of the research by experts and scholars both at home and abroad. The continuous increase of car ownership not only brings convenience to people's lives, but it also poses a threat to people's lives and security of the property. Objective: Vehicle active safety system is the hotspot of current research and development as it plays an important role in automobile safety. Through the analysis of patents and references, we aim to understand the development of an active steering system. In order to improve the development efficiency of the active steering system, the paper proposes a feedback control method of the front-wheel angle. Methods: Based on yaw velocity and center of a mass side angle, the Active Front Steering (AFS) model is established respectively by fuzzy control and sliding mode control under the establishment of seven degrees of freedom vehicle dynamics model and the Dugoff tire model. Results: The simulation results show that both the control algorithm of sliding mode control and fuzzy control can improve the handling stability of vehicle steering on high adhesion coefficient road surface. On the low adhesion coefficient road, the control effect of slide mode control is more ideal while fuzzy control caused larger oversteer. Conclusion: The simulation results show that the control effect of sliding mode is superior to fuzzy control.
Keywords: feedback control